Bit Error Rate Reduction by Smart UWB Antenna Array in Indoor Wireless Communication. - Chen, Chien-Hung (Journal of Applied Science and Engineering)
In this paper, a new ultra wideband circular antenna array (UCCA) combining genetic algorithm to minimize the bit error rate (BER) is proposed. The ultra widened (UWB) impulse responses of the indoor channel for any transmitter-receiver location are computed by applying shooting and bouncing ray/image (SBR/Image) techniques, inverse fast Fourier transform and Hermitian processing. By using the impulse response of multipath channel, the BER performance of the binary pulse amplitude modulation (B-PAM) impulse ratio (IR) UWB system with circular antenna array can be calculated. Based on the topography of the antenna and the BER formula, the array pattern synthesis problem can be reformulated into an optimization problem and solved by the genetic algorithm. Our approach is not only choosing BER as the object function instead of sidelobe level of the antenna pattern, but also considering the antenna feed length effect of each array element. The strong point of the genetic algorithm is that it can find out the solution even if the performance index cannot be formulated by simple equations. Simulation results show that the synthesized antenna array pattern is effective to focus maximum gain to the LOS path which scales as the number of array elements. In other words, the receiver can increase the received signal energy to noise ratio. The synthesized array pattern also can mitigate severe multipath fading in complex propagation environment. As a result, the BER can be reduced substantially in indoor UWB communication system.